Hubungan Sikap Ibu Tentang Pemberian Makanan Bayi Dan Anak (PMBA) Dengan Status Gizi Bayi Bawah Dua Tahun (Baduta) - Fatimah Sari (LPPM STIKES Guna Bangsa Yogyakarta, 2018)
Background: The growth and development in infants is very rapidly. The growth and development can be realized optimally when on the gold period, babies obtain the appropriate nutritional intake of Breast Milk is recommended as one of the exclusive source of nutrition in the first 6 months. Nutrition deficiency is suspected due to a lack of understanding of parents or proper nutritious food to the influence of advertising. They want to break the cycle of malnutrition that causes children short.